Arte della guerra nel Rinascimento: Esempi di ricette di polvere da sparo all’ombra del Palazzo Ducale di Urbino* - Gamba, Enrico; Pietrini, Davide (Chimica nella Scuola, 2023)
The essay analyses the theme of the art of war in the Renaissance with a multidisciplinary approach, paying particular attention to the diversity of firearms and to the methods of preparing gunpowder, both described by Francesco di Giorgio Martini.